MOBILITAS PENDUDUK MISKIN DI DESA TOUURE KECAMATAN TOMPASO KABUPATEN MINAHASA - Azief Putra Dunda; Welson M. Wangke; Martha M. Sendow; Celsius Talumingan (COCOS, 2013)
ABSTRACTAZIEF PUTRA DUNDA. Poor in Rural Population Mobility Touure TompasoMinahasa District with Supervisor Ir. Welson M. Wangke, MS as Chairman,Dra. Martha M. Sendow, Msi and Ir. Celsius Talumingan, MP as a Member.This study was aimed to determine the relationship of the mobility levelbetween poor and poverty people in sub Village Touure Tompaso Minahasaregency.This study was done for three months, beginning in August to October2012 in Touure Village, Tompaso District, Minahasa regency. The data wereconsist of primary and secondary data. The first data were obtained byinterviewing the respondents and the second were obtained from the CentralStatistics Office and District Tompaso. Respondents totaling 60 people chosen atrandom by using Simple Random Sampling.This research was shown that the mobility level is low and made bothends meet in Village Touure. The test resultsusing Chi-Square analysis shownthat there are relationship between the mobility level and poverty where thepoverty rate is low or not a personis poor then performeda high level of mobility.On the contrary that the poor people were low in mobility level.Residents who has a job outside the village have high mobility, becauseof the mobility for working. While the villagers who have low mobility only worksas a farmer, although there is a desire to make mobility out of the village to get abetter job, but from an economic standpoint is not possible to perform mobilityout of the village.